Psychological Factors Explaining Perceived Impact of COVID-19 on Travel - José Magano; Diogo Guedes Vidal; Hélder Fernando Pedrosa e Sousa; Maria Alzira Pimenta Dinis; Ângela Leite (MDPI AG, 2021)
This cross-sectional study aims to determine the psychological factors that contribute to the perceived impact of COVID-19 on travel using a convenience sample (N = 1122) from the general population to whom instruments assessing the perception of the COVID-19 pandemic's impact on travel, anxiety, fear, phobia, risk perception, and stress were applied. The participants were mainly female (65.6%), had not attended university, and who were professionally active, with a mean age of around 30-years-old (M = 31.91, SD = 13.76, Min = 18, Max = 81). The perceived impact of COVID-19 on travel correlates with all of the psychological variables, mainly in terms of the emotional fear of COVID-19. Together with the perceived risk of COVID-19, social phobia due to COVID-19, and COVID-19 stress contamination, these variables explain 20% of the perceived impact of COVID-19 on travel variance. The relationship between COVID-19 stress socio-economic consequences and the perception of the pandemic's impact on travel is moderated by the emotional perceived risk of COVID-19. Fear and perception of this risk explain the impact of the COVID-19 on travel in pandemic times, suggesting that the psychological impact of fear and anxiety induced by the pandemic needs to be handled as a public health priority.